JCV-specific cell-based assays for PML risk assessment in lupus and multiple sclerosis patients with and without natalizumab - Wu, Qi; Mills, Elizabeth A.; Wang, Qin; Mao, Guangmei; Mao-Draayer, Yang (Frontiers in Neurology, 2025)
BackgroundProgressive multifocal leukoencephalopathy (PML) is an opportunistic infection caused by the JC virus and often fatal. Natalizumab is a highly effective therapy for multiple sclerosis (MS) but is linked to a high incidence of PML. The current metrics used to stratify MS patients at risk for PML are incomplete, leading some patients to prematurely discontinue an effective treatment and others to develop PML despite perceived low risk.ObjectiveWe sought to develop a combination of cell-based assays using peripheral blood which can be used to provide a more comprehensive assessment of immune system function and complement existing PML risk metrics.MethodsOur assays measure general and JCV specific responses in CD4+ and CD8+ T cells following antigen stimulation. We examined responses in systemic lupus erythematosus (SLE) and MS patients with and without PML. Our cytotoxicity index (CTI) measures expression of IFNγ and the degranulation marker CD107a on CD8+ T cells, while our OX40 immunity index (OII) measures CD4+ T cell activation, as determined by OX40 and CD25 co-expression.Results and conclusionWe find that the combined metrics can be used to assess JCV immunocompetence, which can distinguish patients with and without PML, and could be used to predict and monitor PML patients from diagnosis onward to facilitate timely intervention.